Optimization of Non-Effervescet Floating Tablets Ranitidine HCL Formula Using Durian Seed Matrix (Durio Zibethinus Murr) Fully Gelatinized Modified Using Simplex Lattice Design Method - Agung Dewantara Putra, I Gusti Ngurah; Setyawan, Eka Indra; Ninditha, Ni Putu Maya; Diva, Made Tresia Pramasta (Green Publisher Indonesia, 2023)
This study investigated the use of fully gelatinated durian seed starch as an excipient in Ranitidine HCl Non-Effervescent Buoyancy Tablets (NEFT). The simplex lattice design method was used to formulate the optimum composition of the formula, including fully gelatinated durian seed starch, PVP K30, and magnesium stearate. Physically modified durian seed starch is expected to increase the release time of active substances in the body. The experiment was conducted for six months by measuring the physical properties of the granule, tablet hardness, solubility, and friability. Results showed that the optimum formula (27.74 mg durian seed starch, 1.5 mg PVP K30, 0.76 mg magnesium stearate) produced ranitidine HCl NEFT tablets with optimal properties. This research may contribute to the development of effective tablet formulations.